Tīna tapasvī : Āgarakara, Vāmanarāva Jośī, āṇi Sāne Gurujī - Padhye, Prabhakar, 1909- (SAMP early 20th-century Indian books project, 1946)
Biographies of Gopal Ganesh Agarkar, 1856-1895, Vāmanarāva Jośī, 1881-1956, and Sane Guruji, 1899-1950, intellectuals from Maharashtra.